Effects of in ovo feeding of chlorogenic acid on antioxidant capacity of postnatal broilers - Pan, Yali; Lin, Hai; Jiao, Hongchao; Zhao, Jingpeng; Wang, Xiaojuan (Frontiers in Physiology, 2023)
In this study, chlorogenic acid (CGA) was injected into the amniotic cavity of chicken embryos to study the effects of in ovo feeding of CGA on the antioxidant capacity of postnatal broilers. On the 17th day of embryonic age, a total of 300 healthy broiler fertile eggs with similar weights were randomly subjected to five groups as follows; in ovo injection with 0.5 mL CGA at 4 mg/egg (4CGA) or 7 mg/egg (7CGA) or 10 mg/egg (10CGA), or sham-injection with saline (PC) or no injection (NC). Chicks with similar body weights hatched from each replicate were selected and reared until heat stress treatment (35 ± 1℃, 8 h/d) at 28 to 42 days of age. The results showed that there was no significant difference in the hatching rate between the groups. After heat stress treatment, 4CGA group showed an improved intestinal morphology which was demonstrated by a higher villus height in the duodenum and a higher villus height/crypt depth ratio in the jejunum. The antioxidant capacity of chickens was improved by in ovo feeding of CGA since 4CGA decreased the plasma content of malondialdehyde (MDA), whereas, it increased the superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase (CAT) activities. Also, the MDA content of the different injection groups had a quadratic effect, with the 4CGA group having the lowest MDA content. In the duodenum, 4CGA injection significantly increased the mRNA expressions of nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase 1 (HO-1), glutathione synthetase (GSS), and SOD1. The mRNA expressions of glutathione reductase (GSR) and GPX7 were significantly increased in all CGA-treated groups, while the mRNA expression of CAT was significantly increased by 4CGA group. The mRNA expressions of epigenetic-related genes, ten eleven translocation 1 and 2 (Tet1 and Tet2), and DNA-methyltransferase 3 alpha (DNMT3A) in the duodenum of 4CGA injected group was significantly increased. The mRNA expressions of Nrf2, SOD1, and Tet2 showed significant quadratic effects with the 4CGA group having the highest expression. In conclusion, in ovo feeding of CGA alleviated heat stress-induced intestinal oxidative damage, which may be related to its regulation of epigenetic mechanisms.